Det kgl. Landhusholdningsselskabs Generalforsamling den 13de December 1877. - la Cour, J. C. (Tidsskrift for Landøkonomi, 2018)
Det kgl. Landhusholdningsselskabs Generalforsamling den 13de December 1877.